ILLOCUTIONARY SPEECH ACTS IN TAYLOR JENKIS REID’S NOVEL MALIBU RISING - Hendriyani, Silvi; Pratiwy, Devi (Universitas Islam Sumatera Utara, 2024)
This research aims to identify the types of illocutionary speech acts found in the main characters' utterances in Taylor Jenkins Reid's novel Malibu Rising. Using Searle’s theory of illocutionary acts, the study examines the contextual meanings behind these acts. A qualitative descriptive methodology was applied, focusing on character dialogues as data. Data collection involved reading and analyzing dialogues, selecting utterances containing illocutionary acts. Analysis followed Miles and Huberman’s framework, encompassing data reduction, data display, and conclusion/verification. Results reveal that the main characters' utterances incorporate five types of illocutionary acts: representatives, directives, declaratives, commissives, and expressives, with directives and expressives being predominant. The research underscores the role of competitive and conflicting speech acts in character interactions, demonstrating how these acts advance the narrative and depict social dynamics. Findings suggest that illocutionary acts in Malibu Rising illustrate internal states, facilitate social interactions, and navigate interpersonal relationships. This study offers insights into the pragmatic functions of language in literature, enhancing understanding of how speech acts reflect real-life communication and contribute to character development and narrative structure. Future research could build on these findings by examining illocutionary acts in various literary genres and comparing their use across different authors and themes.